Bioinformatic investigation of the cost management strategies of five oral microbes. (9th October 2014) - Cross, K.J.; Huq, N.L.; Park, S.H.; Park, J.S.; Pham, P.; Quah, M.; Ranjan, M.; Reynolds, E.C.
Summary Some amino acids are more energetically costly to synthesize de novo, therefore many microbes have evolved to regulate the metabolic expenditure of the cell and reduce the energy burden of extracellular unrecyclable proteins. Several oral bacterial species take up amino acids and peptides obtained from proteolysis of host proteins and hence do not rely only on de novo synthesis. The aim of this study was to investigate if five oral bacterial species implement cost management strategies to reduce the energy burden of extracellular unrecyclable proteins. Since the relative de novo amino acid synthesis costs are proportional to the masses of the amino acids, the energy costs of producing proteins were assessed by calculating the mean amino acid mass for each protein. For Porphyromonas gingivalis, Treponema denticola, Tannerella forsythia, Prevotella intermedia and Streptococcus sanguinis, the outer membrane/extracellular proteins are made up of a much larger percentage of lower average mass amino acids whereas cytoplasmic proteins are made up of a larger proportion of higher average mass amino acid residues. These results are consistent with the five oral bacterial species employing energy‐saving mechanisms in the production of extracellular unrecyclable proteins. Interestingly, the P. gingivalis and S. sanguinis genomes exhibited significantly lower predicted mean amino acid masses compared with those of the genomes of the other three species, suggesting that this may provide them with an energy advantage with respect to protein biosynthetic cost.